The Effect of Inheritance Receipt on Retirement - Brown, Jeffrey R; Coile, Courtney C; Weisbenner, Scott J (The Review of Economics and Statistics, 2010)
This paper provides new evidence on how wealth shocks influence retirement behavior. Economic theory generally posits that leisure is a normal good, yet it is difficult to obtain reliable empirical estimates of the wealth effect because wealth is correlated with numerous unobservable characteristics that affect labor supply. We use inheritance receipt as a wealth shock and find that it is associated with a significant increase in the probability of retirement, especially when the inheritance is unexpected. This evidence has important implications for how public policies, such as pension or tax reform, may influence retirement behavior through the wealth effect.